2017
DOI: 10.3389/fneur.2017.00341
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Intravenous Thrombolysis Rates for Acute Ischemic Stroke and Associated Quality Performance Parameters

Abstract: IntroductionBased on data from the Baden-Wuerttemberg stroke registry, we aimed to explore the diurnal variation of acute ischemic stroke (IS) care delivery.Materials and methods92,530 IS patients were included, of whom 37,471 (40%) presented within an onset-to-door time ≤4.5 h. Daytime was stratified in 3-h time intervals and working vs. non-working hours. Stroke onset and hospital admission time, rate of door-to-neurological examination time ≤30 min, onset-/door-to-imaging time IV thrombolysis (IVT) rates, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…12 In line, Reuter et al found the longest DNT time and the lowest IVT rate between 03:01 and 06:00 am. 9 Furthermore, Kristiansen et al found in-hospital performance measures to be worse in patients admitted during NH. 20 Other studies, however, showed no association of DNT with time of hospital arrival 11 and no deterioration of acute reperfusion therapy rates in candidates for thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…12 In line, Reuter et al found the longest DNT time and the lowest IVT rate between 03:01 and 06:00 am. 9 Furthermore, Kristiansen et al found in-hospital performance measures to be worse in patients admitted during NH. 20 Other studies, however, showed no association of DNT with time of hospital arrival 11 and no deterioration of acute reperfusion therapy rates in candidates for thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This ongoing evolution of acute stroke recanalization strategies will make new concepts of pre-and in-hospital care delivery necessary (21)(22)(23). It seems reasonable to consider the diurnal variation of the stroke for future implementation strategies of MT (7,13).…”
Section: Discussion Of Results For Clinical Practicementioning
confidence: 99%
“…Stroke admission rates have a strong morning peak, which was observed regardless of stroke severity ( Figure 1 , Supplementary Table 1 ) ( 7 ). Absolute admission numbers were highest between 09:01 and 12:00 and lowest between 03:01 and 06:00 for all subgroups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations